1984
DOI: 10.1128/aac.26.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline diffusion through phospholipid bilayers and binding to phospholipids

Abstract: The ability of tetracycline to pass through phospholipid bilayers by diffusion was investigated. Liposomes did not retain enclosed tetracycline. Accumulation of tetracycline was observed with liposomes containing entrapped Tet repressor protein. These results indicate that the drug can pass through lipid bilayers. The antibiotic was also shown to bind to liposomes and isolated phospholipids.Incubation of Escherichia coli cells in medium containing tetracycline leads to uptake and accumulation of the antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…In order to reveal whether ApH-dependent tetracycline accumulation requires a carrier, accumulation of tetracycline in protein-free liposomes was investigated. The downhill diffusion of tetracycline through phospholipid bilayer membranes had previously been reported by Argast and Beck (1). We succeeded in showing that tetracycline accumulation in liposomes is driven by an artificially imposed ApH.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…In order to reveal whether ApH-dependent tetracycline accumulation requires a carrier, accumulation of tetracycline in protein-free liposomes was investigated. The downhill diffusion of tetracycline through phospholipid bilayer membranes had previously been reported by Argast and Beck (1). We succeeded in showing that tetracycline accumulation in liposomes is driven by an artificially imposed ApH.…”
Section: Resultssupporting
confidence: 49%
“…In contrast, Argast and Beck (1,2) showed that tetracycline enters the cytoplasm through simple diffusion because of the nonsaturability of tetracycline uptake and presented evidence for diffusion through phospholipid bilayers. The question is how such simple diffusion leads to the accumulation of tetracycline in cells.…”
mentioning
confidence: 99%
“…Despite their wide application, only little is known about their mode of action, including both their uptake and inhibition of translation [1]. It is assumed that the ability of tetracycline (tc) to diffuse through lipid bilayers [4] and its protonation behaviour along the pH gradient of the cell is sufficient to explain accumulation in Escherichia coli [5,6].…”
mentioning
confidence: 99%
“…According to current concepts, TetA protein functions as a carrier for tetracycline in the excretion of the antibiotic (which enters the cell presumably by passive diffusion [1,2]). This transport of tetracycline was shown to be energy dependent (15) …”
mentioning
confidence: 99%